COVID 19 and the Related Risk with the Apearance of Arterial Hypertension - Freddy Fernando Jumbo Salazar; Génesis Alexandra Zúñiga Cárdenas; Liliana Katherine Sailema López (Medisur)
Arterial hypertension is a chronic inflammatory disease of a vascular nature and systemic and non-transmissible related to COVID-19. The objective was to determine the risk of presenting Arterial Hypertension in patients with COVID-19 through different diagnostic tests, as well as to establish the consequences of inadequate management of cardiovascular disease. The databases: Medline, Scielo, Redalyc, Latindex, SCOPUS, Dialnet, Cumed and Lilacs were reviewed. As a result, it was possible to identify the risk of suffering from hypertension in COVID-19 patients, a common aggravating factor in cardiovascular diseases, among them congestive heart failure or coronary heart disease, in the same way, a non-modifiable risk factor for suffering from arterial hypertension was age, therefore, the greater the age, the greater the risk of morbi-mortality. It was determined that the risk of presenting Arterial Hypertension was cardiovascular disease, which get worse with age and the use of antihypertensive drugs, and it was established that the consequences of inadequate management of this disease affect the person's subsequent lifestyle due to the consequences of it.